APPLICATION OF PROJECT BASED LEARNING LEARNING MODEL WITH MEDIA MIND MAPPING TO INCREASE ACTIVE PARTICIPATION AND LEARNING OUTCOMES OF STUDENTS IN PPKN SUBJECTS - Rochman, Inayah Af’idatul; Murdiono, Mukhamad (International Journal of Social Service and Research, 2024)
This study aims to determine whether using the project-based learning model with mind mapping media can increase students' active participation and learning outcomes in class X D at Madrasah Aliyah Sunan Pandanaran Yogyakarta. The study's findings suggest that using the Project-based Learning Media Mind Mapping Learning Model can raise students' levels of active engagement and learner learning outcomes. The results of the study also suggest that the use of the project based learning media mind mapping learning model can improve students' cognitive and psychomotor learning outcomes both individually and in groups. Specifically, the study contributes to the growing body of educational research by exploring how these combined methods can improve student engagement and academic performance in a high school setting, providing valuable insights for educators looking to adopt innovative teaching strategies in similar educational contexts.